KOMUNIKASI INTERPERSONAL PELAYANAN PUBLIK KELURAHAN KEPUTRAN DALAM MELAKSANAKAN SAPA WARGA PAGI DAN MALAM HARI - APRILLIA, ZHEVANA (Journal Communication Specialist, 2025)
Another fundamental human activity is communication. The importance of communication in human life as social beings cannot be overstated. Humans can relate to one another through communication in many areas of human life, including the home, workplace, market, community, and other places where people congregate. Every human being will be involved in communication at some point. The process of sending, sorting and receiving symbols or messages from one or more people so that messages can be received and understood by listeners and interlocutors can be interpreted as communication. This research uses a qualitative approach, the phenomenological method. The purpose of this research is to know the interpersonal communication of public services in the Keputran sub-district in carrying out greetings to residents in the morning and evening. The result of this finding is that interpersonal communication between co-workers and the community as a whole is considered sufficient, but there are times when certain indicators cannot be applied properly because miscommunication always occurs even though information media has been provided in the form of verbal and non verbal communication.